Domestic Trade Dynamics and Global Competitiveness of Indonesian Halal Products - Desy Arum Sunarta; Riski Apriliani; Fajrin Hardinar (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2026)
The global halal market has expanded rapidly, positioning halal products as strategic assets in international trade beyond their religious significance. This study examines how domestic trade dynamics and institutional conditions shape the international competitiveness of Indonesian halal products. The study employs a systematic literature review (SLR) following the PRISMA 2020 guidelines to identify, screen, assess, and synthesize relevant academic studies on halal trade, certification, governance, market dynamics, and competitiveness. The analysis is theoretically informed by Porter’s Diamond Model and Institutional Theory. The findings indicate that Indonesia’s mandatory halal certification framework can strengthen consumer trust, institutional legitimacy, and market credibility, while simultaneously creating compliance challenges, particularly for micro and small enterprises with limited financial and organizational capacity. The synthesis further identifies domestic market conditions, MSME participation, institutional governance, regulatory coherence, international market access, consumer trust, and Islamic economic principles as interconnected dimensions of halal trade competitiveness. Comparative evidence from the reviewed literature suggests that effective certification systems, institutional coordination, industrial capability, innovation, and alignment between domestic halal policies and international market requirements are important factors in strengthening export competitiveness. The study concludes that enhancing regulatory efficiency, strengthening MSME capabilities, improving institutional coordination, and aligning domestic halal governance with international trade requirements are essential for strengthening Indonesia’s position in the global halal market.